Anemoside B4 Inhibits Vascular Smooth Muscle Cell Proliferation, Migration, and Neointimal Hyperplasia - Shan, Dan; Qu, Ping; Zhong, Chao; He, Luling; Zhang, Qingshan; Zhong, Guoyue; Hu, Wenhui; Feng, Yulin; Yang, Shilin; Yang, Xiao-feng; Yu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Vascular smooth muscle cell (VSMC) phenotypic transformation, proliferation, and migration play a pivotal role in developing neointimal hyperplasia after vascular injury, including percutaneous transluminal angioplasty and other cardiovascular interventions. Anemoside B4 (B4) is a unique saponin identified from the Pulsatilla chinensis (Bge.) Regel, which has known anti-inflammatory activities. However, its role in modulating VSMC functions and neointima formation has not been evaluated. Herein, we demonstrate that B4 administration had a potent therapeutic effect in reducing neointima formation in a preclinical mouse femoral artery endothelium denudation model. Bromodeoxyuridine incorporation study showed that B4 attenuated neointimal VSMC proliferation in vivo. Consistent with the in vivo findings, B4 attenuated PDGF-BB-induced mouse VSMC proliferation and migration in vitro. Moreover, quantitative RT-PCR and Western blot analysis demonstrated that B4 suppressed PDGF-BB-induced reduction of SM22α, SMA, and Calponin, suggesting that B4 inhibited the transformation of VSMCs from contractile to the synthetic phenotype. Mechanistically, our data showed B4 dose-dependently inhibited the activation of the phosphatidylinositol 3-kinase (PI3K)/AKT and p38 mitogen-activated protein kinase MAPK signaling pathways. Subsequently, we determined that B4 attenuated VSMC proliferation and migration in a p38 MAPK and AKT dependent manner using pharmacological inhibitors. Taken together, this study identified, for the first time, Anemoside B4 as a potential therapeutic agent in regulating VSMC plasticity and combating restenosis after the vascular intervention.